Study of Circadian Pattern of Road Traffic Accidents That Occured in the Socialist Republic of Croatia in 1985. - Matešić, Krunoslav (Array, 1988)
The incidence of accidents was surveyed with regard to three type of occurrences: 1) causality involved road accidents (both fatal and non-fatal) ; 2) the incidence of killed road users with regard to the hour of the day ; 3) the incidence of injured road users with regard to the hour of day.